Aquaphotomics monitoring of strawberry fruit during cold storage – A comparison of two cooling systems - Muncan, Jelena; Anantawittayanon, Sukritta; Furuta, Tetsuya; Kaneko, Toshiya; Tsenkova, Roumiana (Frontiers in Nutrition, 2022)
The objective of this study was to use aquaphotomics and near infrared (NIR) spectroscopy to follow the changes in strawberries during cold storage in the refrigerator with electric field generator (super cooling fridge CF) and without it (control fridge CF). The NIR spectra of strawberries stored in these refrigerators were collected over the course of 15 days using portable mini spectrometer and their weight was measured daily. The spectral data in the region of first overtone of water (1300 – 1600 nm) were analyzed using aquaphotomics multivariate analysis. The results showed decrease in weight loss of strawberries, but the loss of weight was significantly lower in SCF, compared to the CF. The reduction of weight loss due to the exposure to electric field was comparable to the use of coatings. The aquaphotomics analysis showed that NIR spectra adequately captured changes in the fruit over the storage period, and that it is possible to predict how long the fruit spent in the storage, regardless of the storage type. During aquaphotomics analysis, 19 water absorbance bands were found to be consistently repeating and to have importance for description of changes during cold storage. These bands defined the water spectral pattern (WASP) multidimensional biomarker that was used for description of the state and dynamics of water in strawberries during storage. Comparison of WASPs of strawberries in CF and SCF showed that the effect of exposure to electric field leads to delay in ripening by around 3 days. This was evidenced by the increased amount of structural, strongly bound water and vapor-like trapped water in the strawberries stored in SCF. This particular state of water in strawberries stored in SCF was related to the hardening of the skin and prevention of moisture loss, in agreement with the decreased weight loss.